CSR Strategy through Kemaslahatan Umat Programs in Building Public Trust - Fathin Anjani Hilman; Dyah Rahmi Astuti; Putri Diesy Fitriani; Izzatin Nihayah (Jogjakarta Communication Conference (JCC), 2026)
This study examines the Corporate Social Responsibility (CSR) strategy of the Indonesian Hajj Financial Management Agency (BPKH) through its Kemaslahata Umat programs in mitigating negative public sentiment and rebuilding public trust. The research adopts a descriptive qualitative approach. Data were collected through observation, document analysis, and digital trace analysis related to BPKH’s CSR activities. The findings reveal that BPKH’s public benefit programs, implemented within the RACE framework (Research, Action, Communication, Evaluation), have proven to be effective as a CSR strategy in fostering public trust in the management of Hajj funds. Public trust is not merely constructed through institutional claims; rather, it emerges from the consistency of tangible actions supported by data-driven research, program implementation that directly addresses societal needs, transparent and empathetic communication, and evaluation processes that are independently verifiable. The novelty of this study lies in demonstrating that the characteristics of Strategic CSR within governmental institutions not only create shared value but also function as a reputational defense mechanism within a sensitive public ecosystem.